PENERAPAN METODE PERSUASIF DALAM PENYULUHAN PERTANIAN TERHADAP PENINGKATAN PENDAPATAN USAHATANI KAKAO DI DESA ONANG UTARA KECAMATAN TUBO KABUPATEN MAJENE - Teddu, sulaiman Sulaiman (LPPM Universitas Malikussaleh - Indonesia, 2022)
Indonesia as one of the largest cocoa-producing countries in the world, with the vast ownership of cocoa is dominated by smallholder plantations, amounting to 92.7 percent of the total area of cocoa plantations in Indonesia. On the other hand the community as the dominant owner, needs to increase the ability to increase the adoption of technology that can be developed at any time. This condition demands an urgent role from agriculture instructors. So that the agricultural program can be optimized in the implementation it is needed in this application.This research has been carried out in North Onang Village, Tubo District, Majene Regency, West Sulawesi Province. This research will be conducted for two months, from March to April 2019. The population and sample of this research are in the North Onang Village, Tubo District, Majene Regency. The total population of cocoa farmers in North Onang Village, Tubo Subdistrict, Majene Regency was 275 people, and then a sample of 10% of the population was taken using the simple random sampling method or 27 random farmers, while the current extension agent in North Onang Village, Tubo District Majene as many as 2 people who are in the Agricultural counseling center.This study aims: 1) To find out the application of the method of extension with persuasive methods in agricultural extension to increase cocoa farming income in Tubo District, Majene Regency, and 2) To find out the dominant form of communication used in the extension system in Tubo District, Majene Regency. While the research uses are as follows; 1) Being input and reference material for the Government of Majene Regency and the Department of Agriculture and Forestry in the implementation of agricultural extension, and 2) As material for agricultural extension workers and other readers in applying extension methods.The results showed that the application of the persuasive method carried out by extension agents using extension methods, namely home / field visits, general meetings, discussion meetings, courses and demonstarsi. Where the five counseling methods have different levels of participation of extension workersKeywords: Methods, counseling, farming, income, and cocoa